Electrospun fibers containing nanodispersions and their use in treating wounds

The submicron emulsion of birch bark extract was prepared by high-pressure homogenization and lecithin emulsion technology, and blended with polymer to form nanofibers. The electrospinning technology was used to process it into electrospinning fibers, which solved the low solubility and gel formation problems of birch bark extract in drug preparations, and achieved high bioavailability and controlled release effects.

CN112533637BInactive Publication Date: 2025-03-11NSC PHARMA GMBH & CO KG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201980041091.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-06-19
Filing Date
2019-06-17
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When preparing drug preparations, birch bark extracts are difficult to prepare suitable forms with sufficient bioavailability, which in turn affects the release and application of drugs.

Method used

By using high-pressure homogenization method and lecithin as an emulsifier, a submicron O/W emulsion containing birch bark dry extract was produced and blended with biodegradable polymer to form nanofibers, which were processed into electrospinning fibers using electrospinning technology.

Benefits of technology

The high bioavailability of birch bark extract is achieved, and the preparation of nanodispersions and the application of electrospinning technology is improved, and the solubility and release control of drugs are suitable for wound healing and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 20046
    Figure 20046
  • Figure 466604
    Figure 466604
  • Figure DEST_PATH_IMAGE001
    Figure DEST_PATH_IMAGE001
Patent Text Reader

Abstract

The present invention relates to a composition based on a nanodispersion, which is preferably further processed into an electrospun fiber comprising such a nanodispersion. The nanodispersion may optionally contain birch bark extract. The electrospun fiber may be particularly useful for treating wounds. For this purpose, the composition containing the electrospun fiber is preferably applied as is or in a spray or foam.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a composition based on a nanodispersion, which is preferably further processed into an electrospun fiber comprising such a nanodispersion. The nanodispersion may optionally contain birch bark extract. The electrospun fiber may be particularly useful for treating wounds. For this purpose, the composition containing the electrospun fiber is preferably applied as is or in a spray or foam.

[0002] US 2010 / 0254961 A1 describes water-soluble electrospun sheets and their use in medicine.

[0003] M. Laszczyk, Freiburg described in his doctoral thesis in 2007 a triterpene dry extract from birch bark (betulaalba cortex) and its potential pharmaceutical use. Birch bark extract has antibacterial activity and also has activity against plasmodium or viruses. In addition, it has anti-inflammatory properties and helps wound healing. Even anti-tumor activity has been described. Despite these highly desirable properties, the use of birch bark extract has been hindered by the difficulty of preparing suitable pharmaceutical preparations. The reasons for these difficulties can be seen from the low solubility of the extract in water and the problems that arise when the extract is dissolved in oil due to the formation of a gel structure.

[0004] WO 2018 / 017576 discloses a water-in-oil foam containing betulin, which comprises a solid birch bark extract dispersed in one or more non-polar liquids. The foam is an emulsified oil gel, which comprises a solid birch bark extract in an oil-in-water emulsion.

[0005] The present invention relates to an improved pharmaceutical formulation containing electrospun fibers, optionally containing birch bark extract. Human skin serves as a barrier between the body and the environment. Therefore, it is susceptible to microbial, thermal, mechanical and chemical threats, which may cause acute or chronic wounds. Triterpenes from birch bark are known to have a variety of pharmacological effects, including enhanced wound healing. Polymer nanofibers made of biodegradable and biocompatible synthetic or natural polymers have been used to develop drug delivery systems for the treatment of various diseases, and one of the potential areas for their use is medicated wound dressings. Therefore, an object of the present invention is to use birch bark dry extracts that have recently been clinically proven to accelerate wound healing and provide bioactive nanofiber wound dressings. First, a submicron O / W emulsion containing an active substance birch bark dry extract is produced by a high pressure homogenization [HPH] method and a lecithin-based phospholipid as an emulsifier. In one embodiment, the emulsion is blended with a commercially available biodegradable and biocompatible polymer to form nanofibers, intended for use in wound therapy using electrospinning technology. The preparation method and emulsion composition (eg polymer / birch bark dry extract / phospholipids / sunflower oil) influence the drug release behavior of the stents, as well as their structural morphology, surface and thermal properties.

[0006] Birch bark extract can thicken oils, which results in so-called oleogels. Oleogels are flexible and deformable systems comparable to hydrogels. In contrast to hydrogels, oleogels are based on a lipophilic phase. Such oleogels can show thixotropic behavior, which means that with rapid stirring, the viscosity decreases, while the viscosity is higher in the absence of applied shear forces. Although there may be some applications where the thixotropic property is helpful, it is not always convenient for pharmaceutical purposes. Therefore, the object of the present invention is to provide an alternative formulation of birch bark extract suitable for pharmaceutical applications.

[0007] It is an object of the present invention to provide alternative pharmaceutical formulations having advantageous properties with regard to biological activity, handling and patient acceptance.

[0008] Birch bark extracts have high levels of triterpenes, which are bioactive plant secondary metabolites. Their various pharmacological properties, such as anti-inflammatory, antiviral, anticancer activity and wound healing effects, are well studied and well described in the literature. These substances are widely distributed in plants, but only the bark of white birch contains up to 34% (w / w) betulin, a pentacyclic lupane-type triterpene with two polar hydroxyl groups on opposite sides of the molecule. A well-characterized, commercially available triterpene dry extract (TE) from birch bark contains about 80% (w / w) betulin. The extract is obtained by accelerated solvent extraction with n-heptane. Other disclosed components of the dry extract are lupeol (LU), erythrodiol (ER), betulinic acid (BA) and oleanolic acid (OA). However, the poor solubility of these triterpenes in polar and non-polar solvents may limit their therapeutic applications due to poor bioavailability. Currently, the available forms for topical application are oleogels and cosmetic water-in-oil creams (e.g. Imlan Creme pur, Birken AG). An oleogel containing sunflower oil received European marketing authorization in January 2016.

[0009] Birch bark is a low-value waste that is produced in large quantities in the forestry industry. Therefore, the starting material for birch bark extract is easily available at low cost.

[0010] Birch bark consists of birch inner bark and birch outer bark. Birch inner bark is denser and more granular than birch outer bark, while birch outer bark is more flexible and more fibrous than birch inner bark. Compared with birch inner bark, birch outer bark is white, thin, tough and has a lower water content. Birch inner bark is darker in color, and the separation of birch outer bark fragments from birch inner bark fragments results in an increased yield of the desired birch bark extract. Birch outer bark contains a high concentration of chemical components of interest, which can be, for example, extracted with a supercritical fluid (preferably with C5-C 10 alkane, preferably heptane).

[0011] Several different extraction methods are known. In one method, triterpenes are extracted from birch bark in hot n-heptane, in which the temperature should be above about 110° C. When the hot n-heptane is cooled, the triterpenes crystallize and can be obtained by filtering and drying the crystals. Other extraction fluids can also be used or CO2 can be used for extraction. Since birch bark extract is a natural product, the composition of the individual components strongly depends on several factors, such as the species of birch from which the bark is obtained, the way in which the birch bark extract is prepared and the subsequent purification steps.

[0012] Birch bark extract contains chemical constituents that can be used for pharmaceutical applications, as antiviral, antibacterial, and anti-inflammatory activities have been reported. Thus, birch bark extract can be used as an antibacterial or antifungal agent and for wound healing.

[0013] Birch bark extract contains several components, depending on the source and production method. The main component is betulin, which is usually present in the extract in an amount of about 75-85% by weight. Lupeol is present in an amount of about 1.5-2.8% by weight, and betulinic acid is present in an amount of about 3.0-4.5% by weight. There are small concentrations of erythrodiol, oleanolic acid and betulinic acid methyl ester. In addition, there are some minor components in birch bark extract, such as betulinaldehyde, ursolic acid, α- and β-boswellic acid, etc. It goes without saying that all components must total up to 100%, however, small trace amounts of solvents used for extraction may be present in the extract.

[0014] Birch bark extract may cause problems in the preparation of pharmaceutical preparations, because the components of birch bark extract can build three-dimensional structures through hydrogen bonding, which cannot be easily made into a suitable form with sufficient bioavailability. Particles of variable size and gel formation may occur, which makes it difficult to prepare suitable pharmaceutical preparations, because the drug components cannot be released in a controlled manner. For example, it may be difficult to apply a thin and evenly distributed layer of oil gel on a wound.

[0015] According to the present invention, a nanodispersion of birch bark extract showing excellent bioavailability is provided. The nanodispersion according to the present invention is preferably prepared by homogenizing a pre-emulsion. The pre-emulsion contains birch bark extract, a pharmaceutically acceptable oil, an emulsifier and an aqueous phase. The oil can be any suitable pharmaceutically acceptable oil, such as castor oil, corn oil, coconut oil, linseed oil, olive oil or peanut oil, wherein sunflower oil is preferred. Such oils are usually purified to meet pharmaceutical standards.

[0016] In a preferred embodiment, the O / W emulsion is composed of four important components, including active substance (birch bark dry extract), phospholipids as emulsifiers, oil phase and aqueous phase. Expected composition and processing conditions have a significant impact on the characteristics of these submicron dispersions. And the property of emulsion-electrospinning nanofibers will be highly controlled by the characteristics of triterpene submicron emulsions. In addition, controlled drug release can be obtained by changing the dispersion properties. The electrospinning of the emulsion containing phospholipids is not usually practiced.

[0017] The emulsifiers used according to the invention are phospholipids. Lecithins ensure the miscibility of liquid-liquid and liquid-solid interfaces and can be derived from commercial lecithins. Lecithins are essential components of the protoplasm of animal and plant cells. In general, different types of phospholipids can be used, such as natural and / or hydrated phospholipids. Preferred phospholipids used according to the invention are phosphatidylcholine, phosphatidylethanolamine, phosphatidylinositol, phosphatidic acid and phosphatidylserine and mixtures thereof. The phospholipids preferably used according to the invention can be referred to, for example, under the name "Phospholipon ®This is primarily hydrogenated phosphatidylcholine, but other commercially available phospholipid products for pharmaceutical purposes may also be used successfully.

[0018] In the nanoemulsion, the phospholipid is present in an amount of 0.01-8 wt%, preferably 0.1-5.0 wt%, relative to the weight of the nanoemulsion. In a particularly preferred embodiment, the nanoemulsion contains about 0.5 wt% birch bark extract.

[0019] In the first step of preparing a nanoemulsion, a pre-emulsion consisting of birch bark extract, oil (preferably pharmaceutically acceptable oil, such as sunflower oil or linseed oil) is mixed with phospholipids and water in a homogenizer. The mixture is then further processed to reduce the particle size of the single droplet particles from an average 2-10 μm droplet size to about <1 μm, and preferably below a submicron size of 400 nm. This can be accomplished by high shear or ultrasonic emulsification, which is very effective in reducing droplet size. Alternatively, high pressure homogenization can be used, wherein a high pressure homogenizer / piston homogenizer is used to produce nanoemulsions of extremely low particle sizes as low as several nanometers.

[0020] The advantage of nanodispersions is that the pharmaceutically active components of the birch bark extract are distributed into very fine particles or droplets, which leads to improved bioavailability. Such nanodispersions can be applied directly to wounds or infected skin, for example by spraying to the affected area of ​​the body. With regard to handling properties, the nanodispersion according to the invention is superior compared to an oleogel. It is a fluid that can even be sprayed or spread onto an infected skin area.

[0021] Electrospinning has attracted more and more attention because it allows drugs to be incorporated into nanofibers by simply mixing active compounds with polymer solutions and then using appropriate equipment processing. The method is well known in the art, and therefore need not be further explained at this point. The fleece produced has unique properties, such as high porosity, high encapsulation efficiency and high surface area to volume ratio, so high drug loading. In addition, the wound dressing made of electrospun fibers simulates the natural extracellular matrix in human tissue, therefore promotes cell proliferation, improves gas exchange, removes exudate, and acts as a physical barrier to prevent microorganisms from entering and dehydrating during wound healing. Preferably, hydrophilic polymer polyvinyl alcohol (PVA) is used, and has been approved by the FDA for human use. PVA polymer has unique properties, such as good chemical resistance, thermal stability, biodegradability, biocompatibility and nontoxicity, which makes it suitable for carrying out electrospinning as a polymer-drug carrier for wound dressings.

[0022] However, encapsulating birch bark dry extract into nanofibers may cause difficulties. For example, early studies have shown that due to its unique structure, the particle size of the dry extract cannot be ground to reach sufficiently small particles, even when high-energy dispersion techniques (such as ultrasound or high-pressure homogenization) are used with aqueous and organic suspensions of the material. This can be solved by processing submicroemulsions and using phospholipids as emulsifiers using birch bark dry extract as active substances by homogenization. It is assumed that this phenomenon seems to be directly related to the use of phospholipids as emulsifiers. In such a situation, it is found that the interfacial tension of the mixture of triterpene extract and phospholipid surprisingly reveals a synergistic effect. The mixture of triterpene extract, phospholipid and oil is processed with a high-pressure homogenizer to produce a dispersion (nanodispersion) of submicron size. These submicron droplets can be used as drug carriers to encapsulate poorly soluble drugs. This can increase the solubility of lipophilic birch bark dry extract, resulting in improved local bioavailability. Furthermore, the phospholipids will also help stabilize the lipophilic birch bark dry extract in the O / W emulsion, thereby increasing its compatibility with the hydrophilic PVA polymer solution prior to electrospinning. In addition, since electrospun nanofibers are also typically in the submicron range, the production of submicron emulsions will enhance better encapsulation and uniform distribution of the birch bark dry extract throughout the polymer matrix.

[0023] Alternatively, the preparation of nanoemulsions can be carried out as follows: a pre-emulsion consisting of a mixture of one or more phospholipids and water is processed in a homogenizer. The mixture is then further processed to reduce the particle size of the single droplet particles from an average 2-10 μm droplet size to approximately <1 μm, and preferably below a submicron size of 400 nm. This can be accomplished by high shear or ultrasonic emulsification, which is very effective in reducing droplet size. Alternatively, high pressure homogenization can be used, wherein a high pressure homogenizer / piston homogenizer is used to produce a nanoemulsion of extremely low particle size as low as several nanometers.

[0024] As mentioned above, the phospholipids in the nanodispersion are distributed into very fine particles or droplets, which leads to improved bioavailability. Such a nanodispersion without birch bark extract can be applied directly to wounds or infected skin, for example by spraying to the affected area of ​​the body. It is a fluid that can even be sprayed or spread onto the infected skin area.

[0025] Furthermore, it can be converted into a foam which is easily and almost contactlessly applied to the skin and which is preferred by many patients.

[0026] For such applications, the nanodispersion is simply filled into a standard aerosol can, a propellant gas such as propane / butane, N2O, dimethyl ether, etc. (2-20 wt%) is added, and the can is closed with a standard foam head.

[0027] In a preferred aspect of the present invention, the nanodispersion is further processed into electrospun fibers, wherein the advantages of the nanodispersion, i.e. the fine dispersion and high bioavailability of birch bark extract, can be preserved for a longer period of time. Another advantage of this embodiment is that such fibers are easy to handle. Electrospun fibers can be easily used to form fleeces or mesh structures that can be applied to wounds. There are many occasions in which such fleeces or meshes are very helpful for treating wounds. For example, if a large area of ​​the epidermis has been injured or even removed, such as in the case of a traffic accident or after a burn, such a fleece structure is very helpful. Alternatively, particularly for the elderly, there are often serious wound problems such as those caused by bedsores. This type of wound is difficult to treat and may cause severe discomfort. For such wounds, fleeces with antibacterial and antiviral activity are very useful, particularly when the fabric structure cannot be removed because the fibers are dissolved and absorbed by the body.

[0028] In a preferred embodiment of the present invention, birch bark extract is prepared into a nanodispersion as described above in a first step. The nanodispersion is then converted into electrospun fibers comprising a fiber forming agent. Preferably, the nanodispersion of birch bark extract is integrated, blended, blended or mixed with a carrier. In particular, the electrospun fibers contain both the pharmaceutically active agent (birch bark extract) and the carrier together in a homogeneous manner.

[0029] During comparative studies of electrospun fibers containing both a pharmaceutically active agent (birch bark extract) and a carrier together in a homogeneous manner, it has been surprisingly found that electrospun fibers made from nanodispersions containing phospholipids without any birch bark extract have excellent properties and can be used to produce a composition for wound treatment. Therefore, other objects of the present invention are electrospun fibers made from nanodispersions containing phospholipids and substantially free of birch bark extract, and their use in the manufacture of a composition for wound treatment.

[0030] Electrospinning is a method of producing fibers, wherein the diameter of the fibers may range from about 50 nm to about 2 μm, preferably from 200 nm to 800 nm. The method involves applying a high voltage to a polymer solution to produce a polymer jet. As the jet passes through air, the jet stretches under electrostatic repulsion, thereby producing nanofibers.

[0031] According to the present invention, a nanodispersion containing phospholipids is formed and mixed with a polymer. Optionally, birch bark extract is first dissolved in a nanodispersion and then mixed with a suitable polymer. The nanodispersion-polymer solution (containing or not containing birch bark extract) is sprayed, for example, with a syringe pump, and the polymer jet is moved to a target where fibers can be collected under a high-voltage field. In such fibers, very small droplets of the nanodispersion are dispersed in the carrier polymer. The nanodroplets of birch bark extract are finely distributed in the polymer matrix, wherein a super-homogenization step may also be helpful. Since the droplets are very small and evenly distributed in the electrospun fibers, the nanodispersion has been converted to a solid state, which allows controlled release of the active ingredients of the birch bark extract. The electrospun fibers maintain the bioavailability of the nanodispersion.

[0032] The polymer that can be used for preferred embodiments must be pharmaceutically acceptable.Such polymer can be selected from polyethylene oxide, polyvinyl alcohol, polyvinyl acetate, polyvinyl pyrrolidone, hyaluronic acid, alginate, carrageenan, cellulose derivatives such as carboxymethyl cellulose, sodium methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl methyl cellulose phthalate, cellulose acetate phthalate, starch derivatives such as hydroxyethyl starch, sodium starch glycolate, chitosan and derivatives, albumin, gelatin, collagen, polyacrylate and derivatives thereof.Particularly preferably, it is easy to dissolve and there is no such polymer of undesirable properties on the wound.Particularly preferably, polyvinyl alcohol or poly (lactide-co-glycolide) are used.

[0033] The advantage of electrospun fibers according to the present invention is that the polymer that forms electrospun fibers together with nanodispersion dissolves in the wound, and does not need to remove the support. According to the specific needs of electrospun fibers, by selecting a suitable polymer or a blend of polymers, the dissolution time can be adjusted. For example, it is well known that by changing the ratio of monomers in polylactide / polyglycolide copolymers, the dissolution time in vivo (or on a wound) can be adjusted. By selecting two or three different polymers and mixing them together into copolymers, the properties of the matrix of the fiber can be accurately adjusted.

[0034] Electrostatic spinning methods for preparing nanofibers of fabrics or fleece-like objects for medical purposes are known. In the electrostatic spinning method, some parameters can be easily adjusted, which can affect the properties of the electrostatically spun fibers. The selection of a suitable voltage has an influence on the properties of the fiber and the viscosity of the nanodispersion mixed with the polymer. In addition, the concentration of the nanodispersion related to the concentration of the polymer, the molecular weight of the polymer, the surface tension and the uniformity and conductivity of the solution has an important influence on the properties of the electrostatically spun fibers.

[0035] Parameters such as feed (flow) rate, applied voltage, syringe tip to collector distance must be optimized, and environmental parameters, especially temperature, humidity and pressure, must be controlled. Depending on the apparatus used to electrospin the fibers, the parameters can be adjusted to obtain the desired properties of the fibers, which are optimized for the intended field of application.

[0036] Since the material used to form the electrospun fibers is a liquid, it may be advantageous to at least partially remove the liquid after the fibers are spun. This can be obtained by adding a highly volatile liquid such as an alcohol or ether or by applying a reduced pressure in the chamber in which the nanodispersion (optionally containing birch bark extract) and the polymer are spun. Under reduced pressure the liquid evaporates, and the fibers dry and harden.

[0037] Electrospun fibers comprising a nanodispersion optionally containing birch bark extract can be advantageously used to treat wounds. Such fibers can be easily converted into fleece of desired thickness and can be easily sterilized. Such sterile fleece or pad or mesh has a high surface area to volume ratio, which results in a high drug loading capacity. Another advantage of electrospun microfibers is the high porosity of the fabric, which can be used as a physical barrier against microorganisms. Therefore, the affected skin area can heal very well, thereby preventing the invasion of unwanted microorganisms from the environment.

[0038] Many wound dressings on the market that contain active agents commonly used for wound healing, such as hydrocolloid or silver dressings, have shown negative effects, such as allergic contact dermatitis, and the use of antibiotic-loaded dressings carries the risk of developing resistance to antibiotics in bacteria.

[0039] Therefore, one object is to develop a dressing (optionally loaded with birch bark extract) with a sustained drug release of about 2 days to about 10 days, preferably about 5 days, which is suitable for use in humans for wound healing, with effective treatment even after long-term use. Since all components are biocompatible and biodegradable in the human body, no invasive and / or traumatic intervention is required to remove the dressing, e.g. in deep wounds. In addition, sustained drug release can lead to less frequent dressing changes, which are painful, especially in the treatment of chronic wounds, and thereby lead to better patient compliance.

[0040] The nanofibers according to the present invention also have other advantages, such as excellent performance in cell adhesion, migration, proliferation and differentiation and similar physical properties of the extracellular matrix. Another advantage of the electrospun fibers according to the present invention is that the birch bark extract is continuously released over time. Due to the distribution of droplets of the nanodispersion derived from the birch bark extract in the electrospun fibers, the pharmaceutical active substance is released according to the dissolution of the electrospun fibers.

[0041] Selecting the appropriate polymer to form the fiber is another measure that determines the rate of dissolution. Some polymers dissolve quickly, while others remain intact for a longer time. As the fiber dissolves, the droplets entrapped within the fiber are released and provide the optimal concentration of the birch bark extract compound exactly where it is needed.

[0042] Depending on the intended use, an appropriate ratio of nanodispersion to polymer is used. Typically the ratio of nanodispersion to polymer is in the range of about 1.0-60 parts by weight of nanodispersion to 99-40% by weight of polymer, preferably 5-50% of nanodispersion to 95-50% of polymer, and particularly preferably 25-45% of nanodispersion to 55-75% of polymer.

[0043] Furthermore, it has been found that even electrospun fibers optionally containing birch bark extract can be converted into foams. As mentioned previously, such foams are easily and almost contact-free applied to the skin and are preferred by many patients.

[0044] In order to provide such a foam formulation, the electrospun fibers must be mixed with water under stirring to form a dispersion. This dispersion is then filled into a standard aerosol can, a propellant gas such as propane / butane, N2O, dimethyl ether, etc. (2-20 wt%) is added, and the can is closed with a standard foam head. The foam that can be provided by such an aerosol can is easily and almost contactlessly applied to all kinds of wounds, such as burns, abrasions or bedsores.

[0045] Further aspects of the invention are shown in the following examples. Example

[0046] In the following examples, different nanodispersions with variable amounts of birch bark extract were used. The nanodispersions were mixed with PVA solution and the mixture was electrospun. The different mixtures of Examples 1-4 are shown below.

[0047]

[0048]

[0049] The properties of the mat obtained with the mixture of Example 1 are shown in Table 1:

[0050]

[0051] Electron micrograph of 10% PVA nanofibers containing phospholipid birch bark extract nanodispersion (60% / 40%) Figure 1 shown.

[0052] Example 5

[0053] In order to demonstrate the superior activity of embodiments of the present invention, a porcine ex vivo wound healing assay has been performed. Briefly, pig ears obtained from a slaughterhouse (for human consumption) were delivered to the laboratory directly after slaughter, cleaned and sterilized. Thereafter, a 6 mm punch biopsy was taken from the plicae of the ear, and fat and subcutaneous tissue were removed. Thus, by removing the 7.1 mm 2 The wound was created in the epidermis and upper dermis in the central area of ​​. Then, the ex vivo wound healing model thus formed was placed with the dermis down on gauze in a culture dish and incubated with Dulbecco's modified Eagle's medium supplemented with hydrocortisone, 2% fetal bovine serum, penicillin and streptomycin at an air-liquid interface. Immediately after wounding, a 4 cm 2 Electrospun mat / 5 μl oil gel, and the model was incubated at 37°C and 5% CO2 for 48 hours. Other steps involved shaking freezing, frozen sections of the central part of the wound healing model were identified using a ruler in the microscope and by checking the total length of the wound during the evaluation period, stained with hematoxylin and eosin. The wound healing process (re-epithelialization) was evaluated by measuring the distance between the wound edge and the tip of the regenerated epidermis with a microscope.

[0054] In the control example, the wound was not treated at all. As a comparison with the prior art, an oleogel was used. A slight improvement could be observed. In addition, a polyvinyl alcohol pad (PVA pad) without birch bark extract was used. It can be seen that the healing properties are better than the control group and even better than the oleogel.

[0055] When the polyvinyl alcohol pad contained birch bark extract, a significant improvement in healing activity was observed. This was seen at 5% birch bark extract (TE) and was more effective at 0.5% birch bark extract (TE).

[0056] Example 6

[0057] a) In further experiments (results not in Figure 2 ), the formulation according to Example 5 was compared with a formulation substantially free of birch bark extract. Surprisingly, the results achieved with the formulation free of birch bark extract were comparable to those with birch bark extract.

[0058] b) In other experiments (results not in Figure 2 ), the formulations containing electrospun fibers according to Examples 1-4 were converted into foam formulations, which were used as described in Example 5. Again, the results achieved with the foam formulations without birch bark extract were comparable to those with birch bark extract.

Claims

1. A pharmaceutical composition for treating a wound comprising a nanodispersion stabilized with at least one phospholipid, wherein the nanodispersion is contained within an electrospun fiber integrated with a pharmaceutically acceptable polymer carrier, wherein the electrospun fibers are converted into electrospun mats, wherein the phospholipid is present in an amount of 0.01-8% by weight relative to the weight of the nanodispersion, The pharmaceutically acceptable polymer carrier is polyvinyl alcohol. wherein the ratio of the nanodispersion to the polymer is in the range of 1.0-60 parts by weight of the nanodispersion to 99-40 parts by weight of the polymer, and wherein the nanodispersion contains 0.5% by weight of birch bark extract, The birch bark extract in the nanodispersion comprises the following components, calculated by weight percentage: and 2-13 wt% of other components derived from birch bark, whereby all components add up to 100 wt%; and The nanodispersion is prepared as follows: phospholipids and water as emulsifiers are mixed with birch bark extract and pharmaceutically acceptable oil, and then the mixture is subjected to high shear or ultrasonic emulsification or high pressure homogenization to obtain a nanodispersion, wherein at least 95% of the particle droplets have a diameter of less than 1 μm.

2. The pharmaceutical composition of claim 1, wherein the at least one phospholipid comprises hydrogenated phosphatidylcholine.

3. The pharmaceutical composition according to claim 1, wherein the components derived from birch bark are oleanolic acid, betulinic acid, and methyl ester of betulinic acid.

Citation Information

Patent Citations

  • Nanoemulsion composition containing vitamin k

    CN102939077A

  • Phospholipid-coated therapeutic agent nanoparticles and related methods

    CN107708670A

  • Water-soluble electrospun sheet

    US20100254961A1

  • Betulin-containing water-in-oil foams and compositions thereof

    WO2018017576A1